2016
DOI: 10.1158/1078-0432.ccr-16-0536
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of the Pharmacokinetics of Crizotinib in Populations of Patients with Non–Small Cell Lung Cancer

Abstract: Crizotinib at a 250-mg twice-daily starting dose appears to be appropriate for all patients irrespective of age, sex, race, body weight, mild or moderate renal impairment, or hepatic function (in the range evaluated: bilirubin ≤ 2.1 mg/dL or AST ≤124 U/L). Clin Cancer Res; 22(23); 5722-8. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The efficacy of crizotinib is optimal at a dose of 250 mg twice daily. A recent study on crizotinib pharmacokinetics revealed that crizotinib at a starting dose appeared to be effective and tolerable, regardless of race, age, sex, hepatic function, or mild to moderate renal impairment (10). Since the hepatitis in the present case was not dose-dependent, the crizotinib dose was increased to the greater extent possible.…”
Section: Discussionmentioning
confidence: 59%
“…The efficacy of crizotinib is optimal at a dose of 250 mg twice daily. A recent study on crizotinib pharmacokinetics revealed that crizotinib at a starting dose appeared to be effective and tolerable, regardless of race, age, sex, hepatic function, or mild to moderate renal impairment (10). Since the hepatitis in the present case was not dose-dependent, the crizotinib dose was increased to the greater extent possible.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, cigarette smoking induces cytochromes CYP1A1/1A2 and is hypothesized to alter anti-EGFR erlotinib pharmacokinetics, resulting in worse clinical outcomes [24, 25]. Crizotinib elimination via CYP1A1/1A2 has not been reported, yet our data suggests cigarette smoking has a potential impact on its pharmacokinetics [26, 27]. Nevertheless, only 29 patients were current smokers at time of crizotinib initiation in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Various factors, including race, affect drug pharmacokinetics. Differences observed between Western and Asian patients in exposure to some drugs may be attributable to factors such as body weight and drug metabolism [13,14]. The recommended Phase II regimen of adavosertib for use in combination with paclitaxel and carboplatin in Western patients is 225 mg bid for 2.5 days [10].…”
Section: Discussionmentioning
confidence: 99%